2003
DOI: 10.1021/ol034571i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Muscothiazoles A and B:  Critical Role of Methyl Group Substitution in RCM-Based Syntheses of Macrocycles

Abstract: [reaction: see text] Muscothiazoles A (2b) and B (2c) have been prepared by two approaches that differ in the order of assembly of the rings. Comparative studies show that substitution of the carbon chains in substrate 5 or 12 (respective precursors to 13-membered and 14-membered rings by RCM), even by a single methyl group, can have a profound effect on increasing the efficiency of the macrocyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Small groups can be effective in exerting a gearing effect in conjunction with a rigid element in the diene backbone. During synthesis of the 13-membered macrocycle 11, Murphy and coworkers found that installation of a methyl group increased RCM yields to 70%, from 15% for its unsubstituted counterpart 10a (Figure 11; both reactions at 7 mM) [101]. A similar proportion of dimers was observed by GC-MS (30% and 22% for 10a and 10b, respectively), the mass balance presumably being accounted for by larger, involatile oligomers.…”
Section: Substituent-induced Conformational Constraintsmentioning
confidence: 71%
“…Small groups can be effective in exerting a gearing effect in conjunction with a rigid element in the diene backbone. During synthesis of the 13-membered macrocycle 11, Murphy and coworkers found that installation of a methyl group increased RCM yields to 70%, from 15% for its unsubstituted counterpart 10a (Figure 11; both reactions at 7 mM) [101]. A similar proportion of dimers was observed by GC-MS (30% and 22% for 10a and 10b, respectively), the mass balance presumably being accounted for by larger, involatile oligomers.…”
Section: Substituent-induced Conformational Constraintsmentioning
confidence: 71%
“…Scheme 2 ignores irreversible cross metathesis reactions, because we observed no evidence for heterodimeric products at 0.01 M. ‡ Crystallographic data for 16b:C 13 The results in Table 1 also suggest the presence of a modest (less than five-fold) Thorpe-Ingold effect. 26 Murphy and coworkers 27 proposed that a single methyl group placed appropriately could increase RCM yields dramatically; the effect is considerably less clear cut in our system. All the cyclooctenone products showed broadened 1 Ha n d 19 FN M Rs p e c t r aa t ambient temperature, characteristic of the anticipated fluxional behaviour.…”
Section: Synthetic Studiesmentioning
confidence: 71%
“…[36][37][38] The exclusive selectivity for 8 can be rationally understood and explained by looking at proposed conformation of oxonium intermediate 9, in which the least hindered approach of the nucleophile led to the important C1, C10 trans configuration of 8. Conversion of 8 to Ambrox ® -like 39 compound 10 was achieved through a ruthenium-catalyzed ring-closing olefin metathesis (RCM) in the presence of 10 mol% ruthenium catalyst at 10 mmol L −1 in dry and degassed, refluxing dichloromethane for 24 h, 40,41 and deacetylation of compound 8 with potassium carbonate gave alcohol 11 in a high yield (85%). Alternatively, the tricyclic lactone molecular scaffold could undergo a variety of further manipulations as a result of the cyclic olefin, such as oxidation, epoxidation, halogenation, and cross-coupling, to afford more complex compounds.…”
Section: Chemistrymentioning
confidence: 99%